2014
DOI: 10.1016/j.brainres.2013.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of Kv2.1 ion channels on spinal motoneurons following peripheral nerve injury

Abstract: Pathophysiological responses to peripheral nerve injury include alterations in the activity, intrinsic membrane properties and excitability of spinal neurons. The intrinsic excitability of α-motoneurons is controlled in part by the expression, regulation, and distribution of membrane-bound ion channels. Ion channels, such as Kv2.1 and SK, which underlie delayed rectifier potassium currents and afterhyperpolarization respectively, are localized in high-density clusters at specific postsynaptic sites (Deardorff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(78 citation statements)
references
References 87 publications
10
68
0
Order By: Relevance
“…The retrograde response of neurons to peripheral nerve interruption is associated with prominent changes in ER organisation42, in the plasticity of synaptic inputs combined with the activation of perineuronal glial cells4344, and increased excitability22. As these changes may be related to altered C-bouton function22, we analysed the impact of sciatic nerve transection on postsynaptic NRG1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The retrograde response of neurons to peripheral nerve interruption is associated with prominent changes in ER organisation42, in the plasticity of synaptic inputs combined with the activation of perineuronal glial cells4344, and increased excitability22. As these changes may be related to altered C-bouton function22, we analysed the impact of sciatic nerve transection on postsynaptic NRG1.…”
Section: Resultsmentioning
confidence: 99%
“…We have also demonstrated that ErbB2 and ErbB4 receptors are present in the presynaptic compartment, suggesting that NRG1 acts as a retrograde signalling molecule in C-type synapses. C-boutons are scarcely investigated structures19, which have been reported to suffer plastic changes in sick MNs after spinal cord injury2021, peripheral nerve lesion22, and amyotrophic lateral sclerosis (ALS)1823242526272829. In addition, mutations in S1R are considered risk factors for familial ALS, and abnormal accumulations of this protein in C-terminals have also been observed in patients with sporadic ALS303132.…”
mentioning
confidence: 99%
“…First, axotomy-like changes in intrinsic membrane properties of motoneurons may be elicited under other experimental manipulations that impair functional interaction with their muscle target but without direct axonal damage, such as chronic blockade of the neuromuscular transmission with either botulinum neurotoxin or bungarotoxin (Pinter et al, 1991;Pastor et al, 2003;Nakanishi et al, 2005). Second, most of the electrical alterations induced by axonal injury in motoneurons, although not all (Romer et al, 2014), are usually reverted by re-innervation of their naive muscle, either targeted or following spontaneous regeneration of motor axons (Kuno et al, 1974b;Foehring et al, 1986a,b;Gonza´lez-Forero et al, 2004b;Bichler et al, 2007a). Rather, recovery may occur even when motoneurons are experimentally forced to innervate de novo a foreign target (Foehring et al, 1987;Foehring and Munson, 1990;Nishimura et al, 1991).…”
Section: Changes In Intrinsic Excitability Of Motoneurons Following Amentioning
confidence: 98%
“…Targeting of sodium channels to the dendritic membrane could indicate the beginning of a change in neuronal polarity, since permanently axotomized motoneurons may develop new processes emanating from the tips of distal dendrites with molecular and structural characteristics that most closely resemble axons (Rose et al, 2001;Meehan et al, 2011). Peripheral nerve injury also induces declustering of somato-dendritic voltage-gated potassium channels (Kv2.1), which under normal conditions are locally aggregated at specific post-synaptic sites in motoneurons (Romer et al, 2014). Other alterations observed in axotomized motoneurons include a narrowing of the range of durations along with a slower decay of the afterhyperpolarization, which are consistent with downregulation of the small-conductance Ca 2+ -sensitive potassium channel subunit, SK2 (Kuno et al, 1974a;Gustaffson, 1979;Nishimura et al, 1992;Pakto et al, 2003), and re-establishment of gap junctional coupling among lesioned cells , features that, again, are more characteristic of motoneurons in embryonic or early postnatal stages of development.…”
Section: Changes In Intrinsic Excitability Of Motoneurons Following Amentioning
confidence: 99%
“…Whether DRG neurons have the capacity to regulate Kv2.1 in this manner, for example through stimuli that trigger acute or sustained hyperactivity of DRG neurons, is as yet unknown and may provide another route to regulating Kv2 channel activity in nociceptive neurons. A recent study has revealed that peripheral nerve injury leads to dephosphorylation of Kv2.1 in spinal α motoneurons, as judged by antibody labeling experiments that showed rapid (within 20 min of nerve injury, the shortest time point examined) changes in phosphorylation-dependent Kv2.1 clustering (Romer et al, 2013). It will be important to determine whether phosphorylation of Kv2.1 expressed in DRG neurons is also regulated by nerve injury, through immunohistochemical analyses aimed at determining the extent of Kv2.1 clustering, or utilizing phosphospecific antibodies specific for individual Kv2.1 phosphorylation sites, or through biochemical analyses of Kv2.1 phosphorylation, including those employing mass spectrometry-based proteomics.…”
Section: Future Studies To Further Define the Role Of Kv Channels In mentioning
confidence: 99%